2020
DOI: 10.1177/0003134820919724
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Length of Stay After Laparoscopic Diaphragm Repair for Isolated Diaphragm Injury After Penetrating Trauma

Abstract: Background Isolated diaphragm injury (IDI) occurs in up to 30% of penetrating left thoracoabdominal injuries. Laparoscopic abdominal procedures have demonstrated improved outcome including decreased postoperative pain and length of stay (LOS) compared to open surgery. However, there is a paucity of data on this topic for penetrating IDI. The aim of this study was to examine the prevalence and outcome of laparoscopic diaphragmatic repair versus open diaphragmatic repair (LDR vs ODR) of IDI. Methods The Trauma Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Their relevance could be missed when performing a primary thoracotomy. If an isolated TID following penetrating trauma is found, laparoscopic repair is feasible and seems to be superior to open repair regarding the length of hospital stay [23]. In our opin-ion, an open surgical approach should still be preferred in severely injured patients after blunt trauma, due to the high rate of intraabdominal concomitant injuries in our patient collective.…”
Section: Discussionmentioning
confidence: 77%
“…Their relevance could be missed when performing a primary thoracotomy. If an isolated TID following penetrating trauma is found, laparoscopic repair is feasible and seems to be superior to open repair regarding the length of hospital stay [23]. In our opin-ion, an open surgical approach should still be preferred in severely injured patients after blunt trauma, due to the high rate of intraabdominal concomitant injuries in our patient collective.…”
Section: Discussionmentioning
confidence: 77%
“…If immediate treatment is mandatory, the treatment of choice often was open surgery [ 14 ]. However, recent literature findings state that laparoscopic repair is just as good or even better because of increased per operative visibility and decreased post-operative pain when compared to open surgery [ 3 ]. Most of these findings include acute trauma care and little is found on patients who experience symptoms at a later stage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Prior adult studies have demonstrated increased use and improved outcomes related to laparoscopic surgery for trauma. [5][6][7][8][9][10][11] For pediatric trauma patients, laparotomy has remained the standard for abdominal exploration and treatment; however, it is associated with an estimated 18% risk of morbidity and 5% risk of mortality. 12 Thus, more recently, increased use of laparoscopy has been employed for diagnostic evaluation of stable pediatric trauma patients as well as for therapeutic interventions including hollow viscous repair and resection.…”
Section: Introductionmentioning
confidence: 99%